Xiao’er Fengreqing oral liquid versus Xiao’er Yanbian granules for pediatric acute pharyngitis/tonsillitis (external wind heat syndrome): protocol and statistical analysis plan for a multi-center, randomized, double-blind, active drug-controlled trial - Liu, Kai; Shi, Lei; Song, Yi-Ke; Du, Yu; Yuan, Yi; Shi, Ze-Yang; Liu, Jian-Ping; Liu, Hui-Lan; Liu, Zhao-Lan (Frontiers in Pharmacology, 2025)
ObjectiveTo evaluate the effectiveness and safety of Xiao’er Fengreqing Oral Liquid (XFOL) for pediatric acute pharyngitis/tonsillitis (external wind heat syndrome) through a multi-center, randomized, double-blind, positive-controlled, non-inferiority clinical trial.MethodA total of 120 participants (60 per group) will be randomized to receive either XFOL or Xiao’er Yanbian Granules (positive control) for 5 days. The primary outcome is the throat pain resolution rate and overall effective rate at Day 5, assessed via the Wong-Baker Faces Pain Rating Scale (WBS). Secondary outcomes include time to symptom onset/resolution, fever resolution time, and traditional Chinese medicine (TCM) syndrome scores. Safety assessments will monitor adverse events, vital signs, and laboratory parameters. Statistical analyses will follow a pre-specified plan, employing non-inferiority testing, survival analysis for time-to-event endpoints, and generalized estimating equations for repeated measures. Missing data will be handled using the last observation carried forward (LOCF) method for effectiveness endpoints, while safety analyses will rely on observed cases.ConclusionThis trial will provide rigorous evidence on the non-inferiority and safety profile of Fengreqing Oral Liquid, supporting its integration into pediatric care for acute upper respiratory infections. Adherence to a predefined statistical analysis plan ensures transparency and minimizes bias, ultimately guiding evidence-based clinical practice for TCM interventions.